Creation of nurse-specific integrated interprofessional collaboration and team-efficiency scenario/video improves trainees' attitudes and performances. Issue 7 (July 2019) - Shiao, Tsu-Hui; Yang, Ying-Ying; Wu, Chen-Yi; Yang, Ling-Yu; Hwang, Shinn-Jang; Huang, Chia-Chang; Liang, Jen-Feng; Kao, Shou-Yen; Lee, Fa-Yauh
Abstract : Background: It is importance to train the interprofessional collaboration (IPC) and team-efficiency (TE) of medical trainees. This prospective study evaluates whether implementation of scenario/video-created workshops in integrated IPC and TE (IIT) program provides additional benefits for IPC-TE skills of nursing trainees. Methods: Mock simulation with two IIT scenarios was held as preintervention IPC-TE assessment. Basic and advanced workshops were arranged for teams of intervention groups for creation of discipline-specific scenario and video. Thirty-six nursing trainees were randomized into teams of five members (three nursing students, one standardized medical student, and one standardized trainees of other profession) in either intervention (scenario plus video and scenario) or control groups. After intervention, all groups received the formal simulation-based assessment using another two IIT scenario. In addition to instructors-based assessment of team' performance in mock and formal IIT simulation using interprofessional team collaboration scale (AITCS), self-assessment of attitudes and program-value score were completed by each trainee, using attitudes toward interprofessional health care teams scale (ATIHCTS) at all stages. Results: Nursing trainees in intervention group gave high satisfaction score to this IIT intervention. In comparison with control group, greater increase in instructor-assessed team performance in the "partnership, " "cooperation, " and "shared decision making" domains of AITCS and the self-assessed "quality of care delivery" and TE domains of ATIHCTS were noted in the intervention groups. The overall improvement was greater in the scenario plus video group than those in the scenario group. Further, these improvements among nursing trainees persisted until follow-up stage at 4-weeks later. Conclusion: For nursing trainees, our study suggested that implementation of a scenario creation-based training resulted in additional improvement in trainee' IPC and TE behaviors and attitudes. Additionally, making video of newly created nurse-specific scenario enhances partnership and cooperation among nursing trainees and their interprofessional team members.